If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3x = 5x + -10x + -10 Reorder the terms: 6 + -3x = -10 + 5x + -10x Combine like terms: 5x + -10x = -5x 6 + -3x = -10 + -5x Solving 6 + -3x = -10 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 6 + -3x + 5x = -10 + -5x + 5x Combine like terms: -3x + 5x = 2x 6 + 2x = -10 + -5x + 5x Combine like terms: -5x + 5x = 0 6 + 2x = -10 + 0 6 + 2x = -10 Add '-6' to each side of the equation. 6 + -6 + 2x = -10 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = -10 + -6 2x = -10 + -6 Combine like terms: -10 + -6 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 2x+11=1x+26 | | f+-30=-67 | | ab+c=f | | G(x)=3f(x)+1 | | 1/3x^1/2=4 | | 1n+72=23 | | x-8=4x-2 | | f(-3)=-x+10 | | 15-43=3(x-1)-4 | | 121c^2-36w^2=0 | | W(6)=250*6 | | 19=p+1 | | -6+3x+8=-210 | | 8a-(-3a)= | | 2x^4+3x^3-2x^2+14x+15=0 | | 4x-8=1+7x | | q-4=69 | | -3(5+5x)=-105 | | 3d=78 | | 1/3(6y-9)=2y=13 | | -14=q3 | | 3.14*35=109.9 | | 3d=73 | | rs+4= | | 50=h+-43 | | 10x-(8/3)-4x=6x | | h=-16t^2+55t+5 | | 3x-3(2x+4)=10 | | 3.14*35= | | h/2=1.63 | | 3(10-4)/(15-3*3) | | -12+20(x)=588 |